2012
DOI: 10.1007/s00213-011-2630-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nucleus accumbens dopamine D1 receptors in ethanol drinking, ethanol-induced conditioned place preference, and ethanol-induced psychomotor sensitization in mice

Abstract: Rationale Dopamine D1 receptor (D1R) signaling has been associated to ethanol consumption and reward in laboratory animals. Objectives Here, we hypothesize that this receptor, which is located within the nucleus accumbens (NAc) neurons, modulates alcohol reward mechanisms. Methods To test this hypothesis, we measured alcohol consumption and ethanol-induced psychomotor sensitization and conditioned place preference (CPP) in mice that received bilateral microinjections of small interference RNA (siRNA)-expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 104 publications
5
55
0
Order By: Relevance
“…Finally, VGLUT1 expression was quantified and glutamatergic signaling examined (by microdialysis and microsensoring) at timepoints corresponding to the key cognitive alterations. The timing of behavioral and neurochemical evaluations was similar to previous studies employing lentiviral shRNA delivery (Bahi and Dreyer, 2012a) and commenced 7 days after intrahippocampal administration, as stable shRNA expression (Kim et al, 2012) and target mRNA (Bahi and Dreyer, 2012b) and protein (Nielsen et al, 2009) knockdown have been reported at this timepoint and importantly appear to be sustained beyond the 30-day duration of the current study.…”
Section: Introductionsupporting
confidence: 62%
“…Finally, VGLUT1 expression was quantified and glutamatergic signaling examined (by microdialysis and microsensoring) at timepoints corresponding to the key cognitive alterations. The timing of behavioral and neurochemical evaluations was similar to previous studies employing lentiviral shRNA delivery (Bahi and Dreyer, 2012a) and commenced 7 days after intrahippocampal administration, as stable shRNA expression (Kim et al, 2012) and target mRNA (Bahi and Dreyer, 2012b) and protein (Nielsen et al, 2009) knockdown have been reported at this timepoint and importantly appear to be sustained beyond the 30-day duration of the current study.…”
Section: Introductionsupporting
confidence: 62%
“…The construction of Drd1a-siRNA expressing lentiviruses has been described previously in detail (Bahi and Dreyer, 2012;Ortiz et al, 2010). In brief, three 19-nucleotide Drd1a-siRNA sequences were added to the U6 promoter by PCR.…”
Section: Construction and Validation Of Lv-drd1a-sirnasmentioning
confidence: 99%
“…Vectors were resuspended in PBS-BSA and stored at À80 C until use (Bahi, 2013;Bahi and Dreyer, 2013). The three distinct Drd1a-siRNA sequences were successfully used to knock-down the expression Drd1a mRNA in the NAc (Bahi and Dreyer, 2012) and proteins in the hippocampus (Ortiz et al, 2010).…”
Section: Construction and Validation Of Lv-drd1a-sirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The CPP apparatus used in the current study has been previously described (Bahi 2012(Bahi , 2013aBahi and Dreyer 2012b;Bahi et al 2013b). In brief, it consists of two equalsized compartments (30×30×30 cm) with a sliding guillotine door in the center of the base.…”
Section: Ethanol-induced Conditioned Place Preferencementioning
confidence: 99%